
计算(a/a平方-b平方-1/a+b)除b/b-a (1-1/1-x)(1/x²-1)
2个回答
展开全部
[a/(a²-b²)-1/(a+b)]÷b/(b-a)
=[a/(a+b)(a-b)-(a-b)/(a+b)(a-b)]÷b/(b-a)
=(a-a+b)/(a+b)(a-b)×(b-a)/b
=b/(a+b)(a-b)×(b-a)/b
=-1/(a+b)
[1-1/(1-x)]×1/(x²-1)
=[(1-x)/(1-x)-1/(1-x)]×1/(x+1)(x-1)
=x/(x-1)×1/(x+1)(x-1)
=x/(x+1)(x-1)²
=[a/(a+b)(a-b)-(a-b)/(a+b)(a-b)]÷b/(b-a)
=(a-a+b)/(a+b)(a-b)×(b-a)/b
=b/(a+b)(a-b)×(b-a)/b
=-1/(a+b)
[1-1/(1-x)]×1/(x²-1)
=[(1-x)/(1-x)-1/(1-x)]×1/(x+1)(x-1)
=x/(x-1)×1/(x+1)(x-1)
=x/(x+1)(x-1)²
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询